Investigation of the putative immunodominant T cell epitopes in coeliac disease - Ellis, H J (Copyright 2003 by Gut, 2003)
Background: Coeliac disease (CD) is an enteropathy mediated by gluten specific T cells which secrete interferon γ (IFN-γ) when stimulated by gluten peptides presented by HLA-DQ2 or DQ8 molecules. Residues 62–75 of α(2) gliadin have been proposed as the immunodominant epitope in the majority of CD patients. Deamidation by tissue transglutaminase (tTG) of the glutamine (Q) at position 65 to glutamic acid (E) is essential for T cell stimulation. Aims: To investigate the antigenicity of this peptide and to establish whether its T cell activating properties can be downregulated by the formation of altered peptide ligands. Patients: Individuals with known CD. Methods: Peptide G4 corresponding to α(2) gliadin residues 62–75, Q-E65 and analogues, substituting each amino acid, except E65, in turn for alanine residues, were synthesised. Small intestinal biopsies were obtained from patients. Biopsies were cultured overnight with a peptic/tryptic digest of gliadin (PTG). Lymphocytes were cultured and restimulated with tTG treated PTG. A T cell line was cloned and clones tested for stimulation and IFN-γ production in response to G4 and its analogues. Results: Some high activity clones were isolated with, for example, a stimulation index (SI) of 15 to G4 and secreting 327 pg/ml of IFN-γ. Substitution of amino acids at several positions abolished or downregulated stimulation and IFN-γ production. Conclusions: Peptide G4 is highly immunogenic. Certain amino acid substitutions in peptide G4 abolish T cell reactivity while others are partial agonists which may have potential in immunomodulation in this condition.